Unfinished The Anthropology of Becoming - Biehl, João; Locke, Peter (Duke University Press, 2017)
This original, field-changing collection explores the plasticity and unfinishedness of human subjects and lifeworlds, advancing the conceptual terrain of an anthropology of becoming. People's becomings trouble and exceed ways of knowing and acting, producing new possibilities for research, methodology, and writing. The contributors creatively bridge ethnography and critical theory in a range of worlds on the edge, from war and its aftermath, economic transformation, racial inequality, and gun violence to religiosity, therapeutic markets, animal rights activism, and abrupt environmental change. Defying totalizing analytical schemes, these visionary essays articulate a human science of the uncertain and unknown and restore a sense of movement and possibility to ethics and political practice. Unfinished invites readers to consider the array of affects, ideas, forces, and objects that shape contemporary modes of existence and future horizons, opening new channels for critical thought and creative expression.Contributors. Lucas Bessire, João Biehl, Naisargi N. Dave, Elizabeth A. Davis, Michael M. J. Fischer, Angela Garcia, Peter Locke, Adriana Petryna, Bridget Purcell, Laurence Ralph, Lilia M. Schwarcz